2019
DOI: 10.1021/acs.inorgchem.9b01258
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Symmetric Bimetallic-Tetracarboxylate Framework: Two-Step Crystallization and Gas Separation Properties

Abstract: A novel noninterpenetrated MOF (NbU-2, NbU denotes Ningbo University) based on an enneanuclear bimetallic cluster was synthesized by postsynthetic uptake of Ni(II) ions of a sodium-based framework via two-step crystallization. This result demonstrated that the hydrolysis of metal ions in the step-by-step synthesis process is controllable and provided a new method for synthesizing high-nuclear metal cluster-based MOF materials. Note that the activated NbU-2 displays relatively high CO 2 /N 2 selectivity, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…The adsorption isotherms of 1 were measured for N 2 at 77 K and CO 2 at 195 K, respectively. 1 shows a type‐IV isotherm for N 2 (Figure S5), which indicates the existence of both micropores and mesopores, agreeing with the relatively large pore sizes of cages as shown in other MOFs [37–39] . The total pore volume of single point adsorption was 0.29 cm 3 g −1 , the value is much lower than the theoretical pore volume (0.70 cm 3 g −1 ), which should be because part of the cavity in the structure is occupied by Me 2 NH 2 + cations, so some voids are inaccessible.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The adsorption isotherms of 1 were measured for N 2 at 77 K and CO 2 at 195 K, respectively. 1 shows a type‐IV isotherm for N 2 (Figure S5), which indicates the existence of both micropores and mesopores, agreeing with the relatively large pore sizes of cages as shown in other MOFs [37–39] . The total pore volume of single point adsorption was 0.29 cm 3 g −1 , the value is much lower than the theoretical pore volume (0.70 cm 3 g −1 ), which should be because part of the cavity in the structure is occupied by Me 2 NH 2 + cations, so some voids are inaccessible.…”
Section: Resultssupporting
confidence: 74%
“…1 shows at ype-IV isotherm forN 2 ( Figure S5), which indicates the existence of both micropores and mesopores, agreeing with the relatively large pore sizes of cages as shown in other MOFs. [37][38][39] The total pore volume of single point adsorption was 0.29 cm 3 g À1 ,t he value is much lower than the theoretical pore volume (0.70 cm 3 g À1 ), which should be because part of the cavity in the structure is occupied by Me 2 NH 2 + cations, sos ome voids are inaccessible. The CO 2 adsorptioni sotherm of 1 reflectsamicroporous materialf eature with ar eversible type-I curve, and the saturated uptakei s 172.5 cm 3 g À1 at 100 kPa (Figure 3a).…”
Section: Gas Sorptionmentioning
confidence: 78%
“…Because of our extensive interest in multifunctional materials, multiple series of polynuclear cluster-based MOFs using a hydrothermal method have been systematically synthesized in our group. Because of the existence of polynuclear clusters, these materials not only can effectively avoid interpenetration of the structure and an increase in the structural porosity but also have a greater chance to bring novel topological structures. ,, Also, most of the polynuclear cluster-based MOFs obtained by our group exhibit excellent structural stability and high selectivity toward C 2 H x /CH 4 , , CO 2 /N 2 , C 2 H 2 /CO 2 , and C 2 H 2 /C 2 H 4 . In addition, many studies have confirmed that it is an effective strategy to adjust the stability of MOF materials by changing the functionality of the organic ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Bimetallic MOFs contain two different types of metal ions or clusters as inorganic nodes in the lattice, which provide a synergistic effect between the different metals. Thus, it increases active sites and results in superior properties which expand the scope of functions of MOFs compared to their monometallic counterparts in applications such as heterogeneous catalysis, selective gas adsorption, energy storage and conversion reactions, luminescence properties, etc. Bimetallic MOGs contain two different types of metal ions assembled by cross-linking coordination with the organic linker at the nanoscale level in the polymeric gel matrix and have shown enhanced intrinsic activity arising from the synergistic effect in the presence of multiple metals. In addition, bimetallic MOGs have more active metal sites owing to the introduction of metal heterogeneity.…”
Section: Introductionmentioning
confidence: 99%